2021
DOI: 10.1021/acs.jpclett.1c03834
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Pore Size Limitation of a Nanoporous Graphene Monolayer Membrane for Water Desalination Assisted by an External Electric Field

Abstract: One efficient strategy for addressing the global water shortage is advanced membrane separation, which depends on the precise pore size being close to the hydrated ion size and other surface properties like charge and polarity. However, it is very difficult to fabricate uniform pores with diameters of <1 nm on monolayer membranes. By applying an electric field (bias voltage) perpendicular to the direction of the pressure difference, herein we demonstrate for the first time that a monolayer nanoporous graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…, where C f and C p the concentrations of ions in the feed and permeate reservoirs, respectively, when half of the water molecules have passed from the feed reservoir to the permeate reservoir. 30 Consistent with the previous studies, no ions can pass through the narrower channel with an interlayer height of 0.68 nm, 11,14 the salt rejection reaches 100% with different partial charges. For the channel with a height of 0.88 nm, the salt rejection slightly decreases for a partial charge q = ±0.4 e and then increases when the partial charge reaches 1.0 e. For h = 1.02 nm, salt rejection obviously decreases as the partial charge increases.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…, where C f and C p the concentrations of ions in the feed and permeate reservoirs, respectively, when half of the water molecules have passed from the feed reservoir to the permeate reservoir. 30 Consistent with the previous studies, no ions can pass through the narrower channel with an interlayer height of 0.68 nm, 11,14 the salt rejection reaches 100% with different partial charges. For the channel with a height of 0.88 nm, the salt rejection slightly decreases for a partial charge q = ±0.4 e and then increases when the partial charge reaches 1.0 e. For h = 1.02 nm, salt rejection obviously decreases as the partial charge increases.…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, in order to reduce the solid−liquid−gas contact interaction, the permeate (right) reservoir contained 1178 water molecules. 11,30 The dimension of the h-BN sheets is 4.34 × 8.0 nm 2 , and the interlayer height of the lamellar h-BN channel is considered as 0.68, 0.88, and 1.02 nm, which corresponds to an effective channel height (h eff ) of 0.34, 0.54, and 0.68 nm. 13,14 The channel height (h) is defined as the distance between the centers of mass of each sheet.…”
Section: Simulation Model and Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when channel height was larger than ~8 Å, became less dependent on channel height, though its magnitude was still as high as 5.8 GPa (for Å). It was expected that further increasing the channel height would further suppress , due to the reduced influence from the channel walls [ 64 , 65 ]. By varying the channel length from 30 to 60 Å (keeping a constant channel height of 10.2 Å), it was found that channel length exerted insignificant impact on water flux and ion retention rate ( Figure 6 c).…”
Section: Resultsmentioning
confidence: 99%